Assessment of health-related quality of life among male patients with controlled and uncontrolled hypertension in Semi Urban India - Patil, Mansi; Hedaoo, Radhika Prashant; Shah, Rohan Pravinbhai; Tauseef, Syed Mohammad; Marzo, Roy Rillera; Ching, Siew Mooi; Lambert, Gavin (Sage, 2023)
The burden of hypertension has been growing over recent decades. In addition to risk of stroke and cardiovascular disease development, data indicates that hypertension may also pose a hazard to the quality of life (QoL) of individuals. Patient reported outcomes such as QoL are often overlooked, with physicians and healthcare professionals not routinely evaluating or customizing treatments according to QoL. In this study we aimed to assess the QoL of hypertensive men (n = 500) undergoing treatment who visited a charitable hospital in Pune, India. Clinic blood pressure was determined and the Mini Cuestionario de Calidad de Vida en Hipertensi³n Arterial (MINICHAL) scale was used to assess the health-related (HR)-QoL of patients. More than half of the participants (62) had uncontrolled hypertension, with a mean systolic blood pressure (BP) of 151 ± 12 mmHg and diastolic blood pressure of 87 ± 6 mmHg as compared to those with controlled blood pressure (mean systolic blood pressure 123 ± 6 mmHg and diastolic blood pressure 84 ± 5 mmHg; P < .01 for both). Predominantly the participants were overweight with body mass index (BMI) of those with uncontrolled hypertension being greater than those with controlled blood pressure (28.4 ± 3.3 kg/m2 vs 23.3 ± 2 kg/m2, P < .01). A reduced QoL was observed for participants with uncontrolled hypertension (overall score 41 ± 5) as compared to those with controlled blood pressure (35 ± 4, P < .001). This was evident on both the mental plane 2.8 ± 2.5 (95% CI = 2.3-3.1) vs 4.1 ± 3.2 (95% CI = 2.5-3.3) and somatic domain 3.4 ± 3.2 (95% CI = 3.0-4.0) vs 4.7.4 ± 3.5 (95% CI = 3.1-4.5) where the QoL was poorer (P < .001) for the uncontrolled hypertensive group. Poorer QoL was observed for people with uncontrolled hypertension. This study indicates that the QoL in patients with uncontrolled hypertension attending an outpatient clinic in India is worse than those with controlled blood pressure. Future studies need to be undertaken to ascertain whether an impaired QoL impacts the outcomes associated with high blood pressure.